Hodgkin’s lymphoma in nuclear medicine: diagnostic and therapeutic aspects - Staak, J. O.; Dietlein, M.; Engert, A.; Weihrauch, M. R.; Schomäcker, K.; Fischer, Th.; Eschner, W.; Borchmann, P.; Diehl, V.; Schicha, H.; Schnell, R. (Nuklearmedizin - NuclearMedicine, 2003)
Today, diagnostic and therapeutic strategies of Hodgkin lymphoma (HL) with positrone emission tomography and radioiummunotherapy include state-of-the-art nuclear medicine which require the cooperation between oncology and nuclear medicine. The benefit of FDG-PET in HL patients with residual tumor masses consists of its high negative predictive value in the therapy control of the disease. The concept of waitful watching in patients with PET-negative residual masses after BEACOPPchemotherapy will be evaluated in a large multicenter trial of the GHSG (German Hodgkin Study Group). Radioimmunotherapy has been performed in patients with CD20-positive Non-Hodgkin lymphoma for 10 years with promising results. HL is also an excellent target for immunotherapy due to the expression of antigens such as CD25 and CD30. Thus, a new radio-immunoconstruct consisting of the murine anti-CD30 antibody Ki-4 labeled with iodine-131 was developed for patients with relapsed or refractory HL.
Keywords: Hodgkin lymphoma; PET; radioimmunotherapy; multicenter trial